Upaya Guru Kelas dalam Mengatasi Kesulitan Belajar pada Pembelajaran Tematik Siswa Kelas I MIN 2 Langkat - Dian Anggeraini; Enda Lovita Pandiangan; Emha Fidiyan Akhadi (STIT Fatahillah, 2023)
The background of this research is because of the learning difficulties experienced by students in the learning process, especially thematic learning. These learning difficulties are the problems that most influence the learning process and learning objectives. Thus the teacher must make various efforts in handling it. The purpose of this study is to find out the types of learning difficulties experienced by students in thematic learning along with the factors that cause these learning difficulties. Furthermore, the research also aims to look at the efforts made by class teachers in overcoming student learning difficulties. This research is a qualitative research with descriptive method. Research data obtained from observations, interviews and documentation. The results of the study found that there were five types of learning difficulties experienced by students in thematic learning. Internal and external factors are the cause of these learning difficulties. Efforts made by the teacher in overcoming learning difficulties by providing action according to the learning difficulties experienced by students. Giving the right action will help students regardless of the learning difficulties they experience, so that students can carry out learning well and achieve the maximum learning objectives.